2015
DOI: 10.1371/journal.pone.0143000
|View full text |Cite
|
Sign up to set email alerts
|

454 Pyrosequencing of Olive (Olea europaea L.) Transcriptome in Response to Salinity

Abstract: Olive (Olea europaea L.) is one of the most important crops in the Mediterranean region. The expansion of cultivation in areas irrigated with low quality and saline water has negative effects on growth and productivity however the investigation of the molecular basis of salt tolerance in olive trees has been only recently initiated. To this end, we investigated the molecular response of cultivar Kalamon to salinity stress using next-generation sequencing technology to explore the transcriptome profile of olive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…Five genes, involved in hormone signaling, were up-regulated: ATB11 and ATP-dependent permease (PDR12) (ABA), germination insensitive to ABA mutant 2 (GIM2) (gibberellins), acetyl serotonin O -methyltransferase (ASMT) (salicylic acid), and SPCL51 (brassinosteroids). There is previous evidence that these genes are involved in drought or salinity tolerance/resistance [ 43 , 44 , 45 ]. PDR12 is a PDR-type ABC transporter that mediates cellular uptake of abscisic acid, and mutant experiments demonstrated that this gene facilitates stomata closure and enhances drought tolerance [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Five genes, involved in hormone signaling, were up-regulated: ATB11 and ATP-dependent permease (PDR12) (ABA), germination insensitive to ABA mutant 2 (GIM2) (gibberellins), acetyl serotonin O -methyltransferase (ASMT) (salicylic acid), and SPCL51 (brassinosteroids). There is previous evidence that these genes are involved in drought or salinity tolerance/resistance [ 43 , 44 , 45 ]. PDR12 is a PDR-type ABC transporter that mediates cellular uptake of abscisic acid, and mutant experiments demonstrated that this gene facilitates stomata closure and enhances drought tolerance [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kalamon led to the identification of 387 unique ion transporter transcripts including 9 Na + transporters, 30 K + transporters and several other transcripts related to proton transport mechanism. 75…”
Section: Sodium and Potassium Channelsmentioning
confidence: 99%
“…Salinity is an important factor affecting plant productivity and constitutes a problem concerning a significant portion of the planet, especially in regions with hot, dry climates [22,23]. The availability of fresh water is one of the major limitations for crop production.…”
Section: Introductionmentioning
confidence: 99%